Comparison of treatment outcomes between slow coagulation transscleral cyclophotocoagulation and micropulse transscleral laser treatment - Young Hoon Hwang; Sharon Lee; Mijin Kim; Jaewan Choi (Scientific Reports)
Abstract This study compared treatment outcomes of slow coagulation transscleral cyclophotocoagulation (SC-CPC, 65 eyes) and micropulse transscleral laser treatment (MPL, 134 eyes) in patients with medically uncontrolled glaucoma. Success was defined as achieving an intraocular pressure (IOP) of 6–21 mmHg with a ≥ 20% reduction from baseline, no reoperation for glaucoma, and no loss of light-perception vision. Visual acuity, number of glaucoma medication, corneal endothelial cell count, aqueous flare values, and complications were analyzed. At 12 months, mean IOP decreased from 32.2 ± 13.4 to 17.9 ± 8.3 mmHg in the SC-CPC group and from 26.4 ± 10.8 to 16.5 ± 6.8 mmHg in the MPL group. No significant changes were observed in visual acuity, medication count, or corneal endothelial cell count. Aqueous flare values increased immediately after the procedure and gradually decreased in both groups, with greater changes at 1 week significantly associated with greater IOP reduction (p < 0.05). Pupillary abnormalities were found in 5 eyes (4.5%) of the MPL group, with no severe complications. The 12-month success rates were 50.1% for SC-CPC and 38.2% for MPL (p = 0.131). Both SC-CPC and MPL effectively controlled IOP, with early postoperative aqueous flare values predicting treatment outcomes.